The acute effect of different warm-up protocols on anaerobic performance in elite youth soccer players - Nedham, R. A.; Morse, C. I.; Degens, H. (The Journal of Strength and Conditioning Research, 2009)
The purpose of the study was to investigate the acute effect of different warm-up protocols on anaerobic performance in elite youth soccer players. Twenty elite youth soccer players (mean age 17.2 ± 1.2 years) performed 3 different warm-up protocols in a random order on nonconsecutive days. Each warm-up protocol consisted of a 5-minute low-intensity jog followed by 10 minutes of static stretching (SS), dynamic stretching (DS), or dynamic stretching followed by 8 front squats + 20% body mass (DSR). Subjects performed a countermovement jump followed by a 10- and 20-m sprint test immediately and at 3 and 6 minutes after each warm-up protocol. Vertical jump performance following DSR was better at 3 and 6 minutes than after DS, which in turn was better than after SS at 0, 3, and 6 minutes (p < 0.05). Jump performance was better at 3 minutes than immediately after, and this improvement was maintained at 6 minutes after DSR (p < 0.05). A better sprint performance was observed after DSR and DS compared with SS immediately and at 3 and 6 minutes following each warm-up protocol (p < 0.05). The results of the study suggest that a dynamic warm-up with the inclusion of resistance enhances jumping ability more than dynamic exercise alone. In addition, a dynamic warm-up produces a superior sprint and jump performance compared to a warm-up consisting of static stretching.